Clinical and laboratory predictors of destructive forms of acute appendicitis: data from a prospective study - M. V. Grinkevich; Yu. V. Chernyakova; Ya. A. Kutsenko (Military Medicine, 2026)
This study analyzes significant clinical and laboratory predictors of destructive forms of acute appendicitis (AA). A prospective study included 100 patients with confirmed AA (58 women, 42 men, mean age ± 16.3 years). In 34 patients, gangrenous or perforated forms were diagnosed intraoperatively. A comparative analysis of clinical and laboratory parameters was performed between groups with destructive and non-destructive forms. Patients with destructive forms had a significantly longer history of the disease before hospitalization (34.5 ± 12.8 hours vs. 14.2 ± 6.5 hours in the non-destructive group, p < 0.05), age over 50 years (64.7 % vs. 31.8 %, p < 0.05), higher levels of leukocytosis (17.4 ± 3.1×10 9 / L vs. 12.1 ± 2.8×10 9 / L, p < 0.05), and C-reactive protein (189.5 ± 65.2 mg/L vs. 52.3 ± 28.7 mg/L, p < 0.05). In the group with destructive forms, procalcitonin >0.5 ng/mL was detected more frequently (73.5 % vs. 15.2 %, p < 0.05). The combination of three or more factors (history >24 h, age >50 years, leukocytosis >15×10 9 / L, CRP >150 mg / L ) was associa ted with a high (87.5 %) risk of developing gangrenous or perforated appendicitis. The obtained data demonstrate that a comprehensive assessment of simple clinical and laboratory parameters allows for highly accurate prediction of the risk of destructive forms of AA and contributes to the timely selection of an adequate surgical strategy.